Understanding wheat farmers' intentions regarding the adoption of integrated pest management - Yadgar Momenpour; Shahla Choobchian; Hassan Sadighi (Sustainable Futures, 2025)
Integrated pest management employs a holistic and sustainable approach to minimize environmental impacts for effective pest control. However, there is limited empirical evidence regarding the implementation and extent of willingness to adopt integrated pest management methods, particularly in developing countries. To address this research gap, this study utilizes an augmented version of the planned behavior model to examine the determinants influencing environmental protection intention among Iranian farmers in adopting integrated pest management practices. This research was descriptive, causal, and correlational, conducted through a cross-sectional survey method on 357 wheat farmers in West Azarbaijan province. The constructs in the original planned behavior model accounted for 51 %, and the extended model accounted for 69 % of the variance in farmers' intention to use integrated pest management practices. According to the findings of structural equation modeling, all constructs, except subjective norm, significantly affect farmers' intention to use integrated pest management. The results suggest that place attachment enhances the relationship between farmers' attitude and intention to use integrated pest management. The model created in this study can serve as a guide for future research and interventions aimed at promoting sustainable agricultural practices worldwide. Policymakers can utilize these insights to develop policies that offer incentives for the adoption of integrated pest management techniques.